2007
DOI: 10.4103/0019-5413.37005
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal intramedullary spinal epidermoid cysts: Report of two cases and review of literature

Abstract: Intramedullary epidermoid cysts of the spinal cord are rare tumors, especially those not associated with spinal dysraphism. About 50 cases have been reported in the literature. Of these, only seven cases have had magnetic resonance imaging (MRI) studies. We report two cases of spinal intramedullary epidermoid cysts with MR imaging. Both were not associated with spina bifida. In one patient, the tumor was located at D4 vertebral level; while in the other, within the conus medullaris. The clinical features, MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 7 publications
(19 reference statements)
1
18
0
Order By: Relevance
“…and enterogenous cysts. 3,[15][16][17] This association reinforces their suspected congenital nature. A congenital dermal sinus was found in four patients in our series, spina bifida in five, diastematomyelia in one, and lipoma in three.…”
Section: Discussionsupporting
confidence: 55%
“…and enterogenous cysts. 3,[15][16][17] This association reinforces their suspected congenital nature. A congenital dermal sinus was found in four patients in our series, spina bifida in five, diastematomyelia in one, and lipoma in three.…”
Section: Discussionsupporting
confidence: 55%
“…The clinical characteristics of primary sacral benign tumors were distinct from the one of spinal benign tumors. Some rare histologic types should be considered when the differential diagnosis [19][20][21][22][23][24][25]. It has been reported that hemangioma was the most frequent benign primary spine tumor in one hospital of China, which was different from the region of sacrum and our database showed giant cell tumor was the most common histological type at the sacrum [1].…”
Section: Location Distribution Of Sacral Tumors and Tumor-like Lesionsmentioning
confidence: 68%
“…Neither of the three conditions' own etiology is not clear. The cause of epidermoid cysts is believed to be the introduction of ectoderm cells arising in early fetal life between 3 and 5 weeks [12]. In 2017, Dai et al reported a series cases of familial lumbar scheuermann disease with idiopathic scoliosis in China, which might indicate the genetic etiology of Scheuermann disease with IS.…”
Section: Discussionmentioning
confidence: 99%